Managing Educational Financing in Islamic Boarding Schools: A Critical Analysis - Hartono; Imam Syafi’i (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the management of educational financing at the Nurul Qarnain Baletbaru Sukowono Jember Islamic Boarding School, which includes three main aspects: planning, implementation, and evaluation of financing. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The main informants consisted of the caretaker of the Islamic boarding school, the treasurer, and the financial manager of the Islamic boarding school. The results of the study indicate that financing planning is carried out through annual deliberations involving all elements of the Islamic boarding school management. The implementation of financing is carried out based on a clear division of tasks and responsibilities, with strict recording and supervision according to the budget post. Financing evaluation is carried out periodically every semester through coordination meetings and financial accountability reports (LPJ), which guarantee transparency and accountability. The most interesting finding of this study is the participatory, efficient, and in-line financing management system in accordance with the principles of modern financial governance, even though it is carried out in a traditional environment such as Islamic boarding schools. This proves that Islamic boarding schools are able to manage finances professionally and sustainably to support the achievement of Islamic education goals.